Pengaruh inovasi produk dan pengalaman Konsumen terhadap kepuasan konsumen serta dampaknya terhadap loyalitas konsumen pada pengguna sabun pembersih wajah - Ganabillah, Herlin Indahtia; Ellena Nurfazria Handayani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine how much influence product innovation and consumer experience have on consumer satisfaction and its impact on consumer loyalty in users of Garnier Sakura White facial cleansing soap in the East Jakarta area. The data collection method used is by giving a questionnaire to 100 Garnier Sakura White facial cleansing soap consumers who have used it at least 3 times in the last 2 months, are at least 17 years old, and live in the East Jakarta area. The sampling technique in this study used a non-probability sampling method and was then selected by purposive sampling. The analysis tool used by researchers is Path Analysis. The results showed a positive influence between product innovation and customer satisfaction. There is a positive influence between consumer experience on customer satisfaction, and there is a positive influence between product innovation on consumer loyalty. There is a positive influence between consumer experience and loyalty and a positive influence between customer satisfaction and consumer loyalty. There is a positive influence of product innovation and consumer experience on customer loyalty through customer satisfaction.